The role of educational games in promoting students’ visit at Sony Sugema Library - Yayu Wulandari; Amina Bina Ilmiah; Hanifa Akmalia Tresnawan; Shafa Nurul Azmi Putrisolichat (Berkala Ilmu Perpustakaan dan Informasi)
Introduction. Sony Sugema Library managed by SD Alfa Centauri faces the challenge of low student interest in visiting. To overcome this, the library increases students' interest in reading by providing facilities such as educational and creative games as the main solution. In addition, the library provides relevant readings, literacy programs such as read aloud, student reading awards, and competitions on national days. This study aims to explain the board game strategy to attract students to the library and increase their involvement in literacy activities